2022
DOI: 10.1039/d1ma01125a
|View full text |Cite
|
Sign up to set email alerts
|

High valence state metal-ion doped Fe–Ni layered double hydroxides for oxygen evolution electrocatalysts and asymmetric supercapacitors

Abstract: Delicate design of nanostructures consisting of multiple components is an important strategy for energy storage materials. In this work, cobalt-doped nickel-iron layered double hydroxide (Fe-Ni3Co2 LDH) assembling from one-dimensional (1D)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The Ce dopant generated a higher ratio of Ni 3+ species to Ni 2+ in Ce-NiCo-LDH compared to pure NiCo-LDH, indicating that more Ni 3+ sites existed in NiCo-LDH, thus increasing the number of highly active catalytic sites of Ni 3+ as the OER catalytic center. Nowadays, more and more non-precious metal doped LDH have been developed as superior electrocatalysts in water splitting, such as W-Ni(OH) 2 /NiOOH [ 45 ], Mo-NiCo-LDH [ 46 ], Fe-NiCo-LDH [ 47 ], and Ta-FeNi-LDH [ 48 ]. Due to the plentiful non-precious metals and its amount of regulation engineering on electrocatalytic performance, a non-precious metal doping strategy provides a vast opportunity to develop excellent electrocatalysts in water splitting.…”
Section: Heteroatom Doping Strategymentioning
confidence: 99%
“…The Ce dopant generated a higher ratio of Ni 3+ species to Ni 2+ in Ce-NiCo-LDH compared to pure NiCo-LDH, indicating that more Ni 3+ sites existed in NiCo-LDH, thus increasing the number of highly active catalytic sites of Ni 3+ as the OER catalytic center. Nowadays, more and more non-precious metal doped LDH have been developed as superior electrocatalysts in water splitting, such as W-Ni(OH) 2 /NiOOH [ 45 ], Mo-NiCo-LDH [ 46 ], Fe-NiCo-LDH [ 47 ], and Ta-FeNi-LDH [ 48 ]. Due to the plentiful non-precious metals and its amount of regulation engineering on electrocatalytic performance, a non-precious metal doping strategy provides a vast opportunity to develop excellent electrocatalysts in water splitting.…”
Section: Heteroatom Doping Strategymentioning
confidence: 99%
“… 48 Another report involved fabricating flexible asymmetric supercapacitors based on NiCo 2 O 4 and FeSe 2 as the cathode and anode, respectively, and operating in a stable operated in a voltage of 1.5 V, which exhibited superior energy storage performance and long-term stability of 1000 successive cycles could be ascribed to the pseudocapacitive charge storage mechanism of both electrodes, which collectively enhanced electrochemical performance substantially. 46 Shao and co-workers 49 recently reported the synthesis of cobalt-doped layer double hydroxide//FeSe 2 /C to construct an asymmetric supercapacitor that delivered superior stability of 84.8% at a discharge rate of 0.3 mA when scanned for long-term cycling of 10 000 with improved energy and power densities. Pandit et al 50 prepared iron selenide via successive ion layer deposition and reaction methods, which revealed a capacity of 671 F g −1 and 431 F g −1 , respectively, when tested using cyclic voltammetry and charge–discharge measurements with substantially-improved rate and cycling performance.…”
Section: Introductionmentioning
confidence: 99%
“…Despite possessing such exceptional properties, their phase stabilization remains a critical issue which requires long reaction processes. , Therefore, an optimization is required in order to have a stable phase with good electrical conductivity (which remains low for LDHs) for faster redox kinetics at their surface-active sites . Alongside, in LDHs, it has been observed that ion transport kinetics remains sluggish due to the absence of sufficient transport channels leading to high ion migration resistance. , This will lead to underutilization of surface and bulk active sites, and thus, redox kinetics remains low. In aqueous electrolytes, H + and OH – follow a Grotthuss transport phenomenon via hopping in H 2 O molecule chains, exhibiting a much higher transport rate than other hydrated ions. , Such transports are benefitted by electrode materials with layered structures where the electrode also paves channeled pathways.…”
Section: Introductionmentioning
confidence: 99%
“…32 Alongside, in LDHs, it has been observed that ion transport kinetics remains sluggish due to the absence of sufficient transport channels leading to high ion migration resistance. 33,34 This will lead to underutilization of surface and bulk active sites, and thus, redox kinetics remains low. In aqueous electrolytes, H + and OH − follow a Grotthuss transport phenomenon via hopping in H 2 O molecule chains, exhibiting a much higher transport rate than other hydrated ions.…”
Section: Introductionmentioning
confidence: 99%